Evaluación hacia un plan de gestión de residuos sólidos domiciliarios en el distrito de Indiana provincia de Maynas 2019 - Zuta Pinedo, Lizbeth (2022)
The present work was developed in the District of Indiana, county Maynas; department Loreto whose coordinates are 3º30`02 `` S 73º03`28 ``, the objective was to carry out the evaluation of the domiciliary solid residuals generated in the District the investigation it was of quantitative and type, the design was not experimental, prospective and traverse, the population was conformed by all the housings that you/they pay their municipal wills and the sample was of 53 housings, being ended up concluding: of the participants in the work the (66%) they manifest that there are not containers of garbage, the (68%) they separate their garbages, the residuals more reutilizables are the plastic bottles (49%), the (83%) he/she receives the service of public cleaning and he/she doesn't also know the final destination of the garbage, the (100%) he/she pays municipal wills and he/she would want to participate of a segregation program with the municipality, all the (100%) they manifest that a wrong handling of solid residuals causes illnesses in the population, the illness more related to this wrong handling they are the breathing ones (41,5%) you present especially in old men and children, The GPC for inhabitant per day is of (0.89Kg/hab./día) having a projection of (4.45 T/día), (133.5 T/mes) and ( 1,624.25 T/anual), the biggest quantity in residuals not generated dangerous they are (94,14%) being the most representative in the sample the organic residuals (78,31%), therefore the hypothesis is accepted outlined in the investigation work.